Evaluation of stocking density on water quality parameters in rearing of Beluga (Huso huso) - Rafatnezhad, S.; Falahatkar, B. (2011)
The potential effects of stocking densities (1, 2, 4, 6 and 8kg/m -2 ) of Beluga (Huso huso) was investigated on water quality and growth factors of the fish. Feed was offered three times daily using a commercial diet to the juvenile fish at the average initial weight of 93.13±1.04g (±SE) for a period of 8 weeks. The final biomass was 4.0, 6.5, 11.0, 14.5, 17.1kg/m -2 from the lowest to the highest densities, respectively. At the termination of the experiment, the mean weight reached 362.4±6.9, 319.7±2.1, 267±9.2, 242.1±6.2 and 211.1±4.1 in densities of 1 to 8kg/m -2 , respectively. Results of the present study showed that growth parameters, including: Final weight (W), body weight daily (BWD), weight gain (WG), condition factor (CF) and feed efficiency (FE) had significant differences among the treatments (P<0.05). Water quality indices including nitrite (NO2), ammonia (NH3), nitrate (NO3) and dissolved oxygen (DO) showed significant differences among the treatments affected by different densities, while other water quality parameters including temperature and pH showed no significant difference (P>0.05). Results showed that stocking densities have major effects on water quality and growth indices of Beluga juveniles. Published